2005
DOI: 10.1590/s1519-566x2005000300020
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA divergence between wild and laboratory populations of Anopheles albimanus Wiedemann (Diptera: Culicidae)

Abstract: Divergencia del ADN Mitocondrial entre Poblaciones del Campo y de Colonia de Anopheles albimanusWiedemann (Diptera: Culicidae)RESUMEN -Las colonias de laboratorio facilitan el estudio de los insectos vectores; sin embargo, se ha sugerido que tales colonias de insectos no son representativas de las poblaciones naturales, llevando en algunos casos, a interpretaciones erróneas respecto a la variación intraespecífica entre los individuos. En el presente estudio se evaluó la variabilidad del gen mitocondrial citocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…A previous study had demonstrated strong loss of polymorphisms and considerable divergence from natural populations in a 20-year old laboratory colony of a different mosquito, the neotropical species A. albimanus [22]. We examined to what extend the Yaoundé strain mosquitoes are representative of local populations, by determining the respective genetic diversities and calculating their genetic distance (divergence) from field-collected local A. gambiae .…”
Section: Resultsmentioning
confidence: 99%
“…A previous study had demonstrated strong loss of polymorphisms and considerable divergence from natural populations in a 20-year old laboratory colony of a different mosquito, the neotropical species A. albimanus [22]. We examined to what extend the Yaoundé strain mosquitoes are representative of local populations, by determining the respective genetic diversities and calculating their genetic distance (divergence) from field-collected local A. gambiae .…”
Section: Resultsmentioning
confidence: 99%
“…However, the genetic composition of these soybean aphid laboratory populations is unknown. Comparisons of laboratory and field populations in other systems have documented less genetic diversity and higher levels of genetic divergence among laboratory and field populations (Lanzaro et al , 1998; Fuller et al , 1999; Arias et al , 2005; Kim et al , 2007). This is expected, since laboratory populations likely contain lower effective population sizes, increased inbreeding pressures and may suffer from founder effects, depending on the initial population size.…”
Section: Introductionmentioning
confidence: 99%
“…A second scientific concern is that vector populations established within SFS will likely be considerably smaller than those in the wild and thus experience inbreeding and a resultant reduction in genetic diversity which could impede fitness. It is well known that genetic diversity within insect vectors can be considerably reduced during laboratory colonization [ 84 - 86 ]. Free-living populations established within SFS may be considerably larger than typical laboratory colonies and thus avoid a similar intensity of inbreeding, however it is unlikely they will escape some bottle-necking and an associated loss of diversity from founder populations.…”
Section: Discussionmentioning
confidence: 99%